An Electrochemical Aptasensor for the Detection of HER2 as a Breast Cancer Biomarker Based on Gold Nanoparticles-Aptamer Bioconjugates - Yeni Wahyuni Hartati; Sari Syahruni; Shabarni Gaffar; Santhy Wyantuti; Muhammad Yusuf; Toto Subroto (Indonesian Journal of Chemistry, 2021)
Inaccurate diagnoses contributes to the high mortality rate of breast cancer. Human epidermal growth factor receptor 2 (HER2) is overexpressed in breast cancer tumors at around 20–30%. This study aims to develop an electrochemical biosensor for HER2 based on a gold nanoparticle-aptamer bioconjugate (AuNP@HER2 aptamer) and investigate the interaction between DNA aptamer and HER2 using computational methods. The bioconjugate was synthesized using maleimide and polyethylene glycol as a linker. The –NH2 group of cysteamine that modified the gold electrode can form a covalent bond with the bioconjugate maleimide. The interaction of the bioconjugated aptamer with HER2 was measured electrochemically based on the [Fe(CN)6]3−/4− redox system. The limit of detection, the linear range of HER2, precision, and accuracy in this study were 1.52 ng mL–1, 0.01 to 15.0 ng mL–1, 0.1298, and 94.06%, respectively. The structure of the DNA aptamer was modeled using mFold, Assemble2, and Chimera, with the interaction between the DNA aptamer and HER2 explored by NPDock. The modeling of the aptamer with HER2 showed that electrostatic interactions dominated the attractive forces. The resulting interaction pattern can be used as a template to improve the binding energy of the aptamer, thus providing insight into the development of aptamer-based biosensors.